Inclusive and sustainable community development and poverty reduction: An empirical study of Sindh, Pakistan. Issue 1 (May 2020) - Iqbal, A; Khan, A A
Abstract: The underdeveloped communities and multi-dimensional poverty are the most common dilemmas of developing countries. The study aimed to determine the inclusive and sustainable community development and poverty reduction, empirical evidence of the selected districts of the Sindh, Pakistan. The research has surveyed in five districts of Sindh and collected data from 230 respondents. The research is based on quantitative investigation through primary data collection from five selected districts of Sindh province of Pakistan, followed by descriptive and inferential analysis on SPSS. A total of three research questions representing different aspects of integrated and sustainable community development and poverty reduction are answered from the results. The study has explored that inclusive and sustainable community development and multi-dimensional poverty has significant positive relationship. The research also points to the significance of the livelihood creation on community development and poverty reduction. A set of recommendations is outlined from the results for effective and efficient policymaking in poverty reduction and community development.